2000
DOI: 10.1002/1097-0282(2000)55:4<254::aid-bip1001>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

The human interferon ? species and receptors

Abstract: Interferon (IFN) was approved by the U.S. Food and Drug Administration on June 5, 1986. As the first biotherapeutic approved, IFN‐α paved the way for development of many other cytokines and growth factors. Nevertheless, we have just touched the surface of understanding the multitude of human IFNs. This paper reviews the history of the purification of human leukocyte IFN and key aspects of our current state of knowledge of human interferon α genes, proteins, and receptors. © 2001 John Wiley & Sons, Inc. Biopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
121
0
3

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 218 publications
(352 reference statements)
0
121
0
3
Order By: Relevance
“…Two types of IFNs, type I and II, are defined by their interaction with cognate receptors, type I or II receptors, respectively (Pestka, 1997;Stark et al, 1998 (Pestka, 2000). Although each receptor requires specific signal transduction components, both receptors interact with JAK family protein tyrosine kinases that phosphorylate (Stark et al, 1998;Samuel, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Two types of IFNs, type I and II, are defined by their interaction with cognate receptors, type I or II receptors, respectively (Pestka, 1997;Stark et al, 1998 (Pestka, 2000). Although each receptor requires specific signal transduction components, both receptors interact with JAK family protein tyrosine kinases that phosphorylate (Stark et al, 1998;Samuel, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…1 In addition to its critical roles in host defense, IFN-a has also been demonstrated to have several central nervous system (CNS) effects ranging from increased neuronal excitabilities 2 and regulation of temperature, 3 circadian rhythm 4 and sleep 3 to ingestive behavior 5 and emotion. 6 Despite wide therapeutic application of IFN-a in chronic viral infections and in several types of malignancies, there is mounting evidence that IFN-a is associated with brain damage in several clinical conditions including HIV-associated dementia, 7 CNS lupus 8 and familial Aicardi-Goutieres syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…The main question at issue is whether their activity is redundant or they are characterized by unique functions (6). Studies of the biological effects of natural IFN subtypes have shown that their activities can vary greatly (7)(8)(9)(10). IFN-␣8, for example, is the most potent antiviral protein (11), while IFN-␤ has a higher potency in inhibiting the growth of certain tumors and is used in the treatment of multiple sclerosis (12)(13)(14).…”
mentioning
confidence: 99%